Induction of foxp3 During the Crosstalk Between Antigen Presenting Like-Cells Mhcii+ Cd83+ and Splenocytes Cd4+ Igm− in Rainbow Trout - Imarai-Bahamonde, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In fish, the spleen is one of the major immune organs in the animal, and the splenocytes could play a key role in the activation and modulation of the immune response, both innate and adaptive. However, the crosstalk between different types of immune cells in the spleen has been poorly understood. In this work, an in vitro strategy is carried out to obtain and characterize mononuclear splenocytes from rainbow trout, using biomarkers associated with lymphocytes (CD4 and IgM) and antigen-presenting cells (CD83 and MHC II). Using these splenocytes, co-cultures of 24 and 48 h are used to determine the gene expression of master transcriptional factors that coordinate the polarization of T cells (t-bet, gata3, and foxp3). The results show a proportional upregulation of foxp3 (compared to t-bet and gata3) in co-cultures (at 24 h) of IFNγ-induced splenocytes with and without stimulation of Piscirickettsia salmonis proteins. In addition, foxp3 upregulation was established in co-cultures with IFNγ-induced cells and in cells only stimulated previously with P. salmonis proteins at 48 h of co-culture. These results show a potential communication between antigen-presenting-like cells and lymphocyte in the spleen, which could be induced towards a Treg phenotype. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.